Dynamics and Vibration Analysis of a Rotor-Bearing System in a Turbofan Engine with Emphasis on Bearings Modeling - Rahmani, Hossein; Elhami, Mohammadreza; Petrudi, Amin Moslemi (European Journal of Computational Mechanics, 2022)
In this research, while investigating the vibration analysis of rotary axes, we specifically investigate the rotor of a turbofan engine used in the industry. The features of this rotor range are high-performance, lightweight, and low-vibration range. These three factors are in contradiction with each other, resulting in a thorough examination of the total vibration of the complete turbofan rotor. To achieve this, various parameters such as the concentration of properties, rotational inertia, gyroscopic torque, rotational loading, effects of unbalanced mass, crevillous effects, bearing flexibility, etc. have been studied in modeling. The rotor’s natural frequencies, along with the critical velocity, are plotted as well as the shape of its modes. The software is required to perform the computations written by Ansys software and after ensuring its accuracy.